2018
DOI: 10.1016/j.bpsc.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated and Premature Aging Characterizing Regional Cortical Volume Loss in Human Immunodeficiency Virus Infection: Contributions From Alcohol, Substance Use, and Hepatitis C Coinfection

Abstract: HIV infection itself may confer a heightened risk of accelerated brain aging, potentially exacerbated by HCV coinfection and substance dependency. Confirmation would require a prospective study with a preinfection baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 59 publications
5
78
0
Order By: Relevance
“…While some brain volumetric studies reported significant contributions of such factors to brain integrity (e.g., Garcia‐Garcia et al, ; Holz, Laucht, & Meyer‐Lindenberg, ; Kesler, Adams, Blasey, & Bigler, ), the current study did not find relations between variables differing among the three groups listed in Table and VLp volume. Similarly, extensive analyses performed in large, longitudinal data sets of AUD (Sullivan et al, ) and HIV (Pfefferbaum et al, ) groups relative to healthy controls did not find significant contributions of such factors to global brain integrity.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…While some brain volumetric studies reported significant contributions of such factors to brain integrity (e.g., Garcia‐Garcia et al, ; Holz, Laucht, & Meyer‐Lindenberg, ; Kesler, Adams, Blasey, & Bigler, ), the current study did not find relations between variables differing among the three groups listed in Table and VLp volume. Similarly, extensive analyses performed in large, longitudinal data sets of AUD (Sullivan et al, ) and HIV (Pfefferbaum et al, ) groups relative to healthy controls did not find significant contributions of such factors to global brain integrity.…”
Section: Discussionmentioning
confidence: 95%
“…By contrast, in HIV and alcoholism comorbidity, poor performance on tests of explicit (immediate and delayed) and implicit (visuomotor procedural) memory are associated with smaller thalamic volumes (Fama et al, ). Indeed, the thalamus has often been highlighted as a specific target of HIV [volume deficits: (Heaps et al, ; Janssen et al, ; Pfefferbaum et al, ; Pfefferbaum et al, ; Pfefferbaum et al, ); reduced glucose metabolism: (Hammoud et al, )], possibly related to CD4 count (Heaps et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal studies confirm cross‐sectional reports of regional volume loss that must be taken into account in assessing the effects of pathology in aging adults. When aging is compounded with alcohol use disorder (AUD), controlled studies have identified age‐alcoholism interactions, where age‐related cortical gray matter and white matter volume declines accelerate in alcoholic participants compared with unaffected controls . The age‐alcoholism interaction may also be relevant to motor performance, which declines decidedly with aging (eg,), may accelerate in older alcoholics, and is likely to have a cerebellar substrate …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, using a matched subset of T1‐weighted MRIs (N = 263) from reports focused on the cerebral structures of alcoholic and control groups, the cerebellar corpus medullare was subjected to two quantification approaches. The first identified the white matter boundaries of the cerebellum, measuring the full volume of the corpus medullare.…”
Section: Introductionmentioning
confidence: 99%